2019
DOI: 10.1186/s12883-019-1399-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of paroxysmal sympathetic hyperactivity (PSH) on the functional outcome of neurological early rehabilitation patients: a case control study

Abstract: Background Paroxysmal Sympathetic Hyperactivity (PSH) is a frequently observed condition among critically ill patients on intensive care units. According to different studies, PSH is associated with worse recovery and increased mortality in acute-care facilities. In this monocentric, retrospective case-control study, we investigated whether this association also applies to post-acute neurological early rehabilitation. Methods The study included n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
9
1
1
Order By: Relevance
“…In previous literature about brain injuries, PSH is more common in males (10), younger patients (14-16), and patients with lower GCS scores (4,11). However, no significant risk factors were found in this study, although patients with PSH tended to be younger (P=0.084).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In previous literature about brain injuries, PSH is more common in males (10), younger patients (14-16), and patients with lower GCS scores (4,11). However, no significant risk factors were found in this study, although patients with PSH tended to be younger (P=0.084).…”
Section: Discussioncontrasting
confidence: 65%
“…In EIR model, the absence of descending inhibition results in exaggerated spinal reactivity, with sympathetic efflux triggered by non-nociceptive peripheral stimuli. Recognition of PSH is important, because it's not rare in severe brain injury, associated with increased mortality, higher healthcare costs, longer hospitalizations, and poorer outcomes (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The cause of increased mortality of PSH in severe TBI patients may result from those who did not respond to treatments rather than the complication itself, which leads to a prolonged duration of this complication, resulting in metabolic disorders or malnutrition and the deterioration of neurological condition occurring eventually (10,11). However, a most recent casecontrol study, which was not consistent with regard to the effects of outcomes, revealed that the occurrence of PSH symptoms was not associated with more complications and higher mortality (12). Because of a lack of unified management process of PSH after TBI, between-study differences may ultimately emerge (3).…”
Section: Introductionmentioning
confidence: 99%
“…In concordance with previous studies, our study too has shown that PSH patients have longer period of stay in hospital. 13,29,30 Mathew et al 31 concluded that the presence of PSH in patients with severe TBI was associated with a prolonged hospital stay, more deaths, and unfavorable outcome. Patients often are more vulnerable to infections and spend longer times on ventilators, which can lead to an increased risk of various lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 However, some studies have found that PSH was not an independent predictor for the increased morbidity or poor clinical outcome. 4,8,13 Several intracranial pathologies, such as seizures, hydrocephalus, and hypoxia, invariably have overlapping manifestations with PSH. Hence, under-recognition and misdiagnosis frequently occur in clinical practice.…”
Section: Introductionmentioning
confidence: 99%